Special issue: Supply chain and logistics decisions under environmental aspect - Neslihan Demirel (Journal of Industrial Engineering and Management (JIEM), 2017)
This editor's note has a twofold objective: (1) to present a brief summary about the environmental issues in supply chain and logistics decisions (2) to present general information about the papers published in the special issue.
Keywords: 650